Transplantation of heterozygous familial hypercholesterolemia living donor liver resulting in early myocardial infarction: a possible dangerous link - Kholaif, Naji; Batha, Lin; Elmahi, Isra; Alnaser, Sulaiman; Alzaher, Sultan; Almallohi , Norah; Alhussein, Mosaad; Alhalees, Dana; Alshehri, Ahmed (Monaldi Archives for Chest Disease, 2024)
Living donor liver transplantation (LDLT) is a lifesaving procedure that is often curative for several liver diseases. Familial hypercholesterolemia (FH) is a metabolic disease that results from an autosomal dominant mutation in the low-density lipoprotein receptor; yet, young patients with FH can live years without detection. Herein, we report a case of a patient who developed early myocardial infarction (MI) after having a transplant from a donor with undetected heterozygous FH. This was a 67-year-old female with non-alcoholic steatohepatitis-related liver cirrhosis, free from coronary artery disease, who underwent LDLT from her daughter, a 45-year-old female with no past medical history. One year post-transplant, she presented with an acute MI with a large atherosclerotic burden. Genetic analysis confirmed heterozygous FH in the donor but not in the recipient. This case emphasizes the importance of incorporating a thorough clinical history and lipid profile into pre-transplant testing for both the recipient and donor, as well as aggressive lipid-lowering therapy post-transplantation to avoid cardiovascular complications.